PENGARUH METODE BERCERITA MENGGUNAKAN WAYANG MARIONET TERHADAP PERILAKU MORAL ANAK USIA 5-6 TAHUN DI TK PERTIWI DWP SETDA PROVINSI RIAU - Mandasari, Fitriza; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Based on the results of the field observation on the moral behavior of children has not developed optimally so it is necessary to apply the method of telling stories using wayang marionet. This study aims to determine the effect of storytelling method using marionet puppet children aged 5-6 years in TK Pertiwi DWP Setda Riau Province. The sample used in this study 15 Children. The data collection technique used is observation. Data analysis technique used t-test with SPSS 17.0 program. The research hypothesis is the storytelling activity using wayang marionet has an influence on moral behavior of children aged 5-6 years in TK Pertiwi DWP Setda Riau Province. This can be known from the analysis of data obtained tcount = 32,337, ttable = 2,145 and Sig. (2-tailed) = 0.000. because Sig. (2-tailed) = 0.000 <0,05 it can be concluded that there is influence of moral behavior of children after being treated using the method of telling story using wayang marionet in learning process. So it means Ho is rejected and Ha accepted which means there is a difference between before and after doing experiments using storytelling method using wayang marionet. The influence of storytelling method using wayang marionet to moral behavior of children aged 5-6 years in TK Pertiwi DWP Setda Riau Province amounted to 39,44%.Keywords: Moral Behavior, Marionet Puppet